Ameliorative effect of black tea extract on the skin of D-galactose-induced aging mice - Zheng, Xiaojie; Deng, Wenbin; Wang, Xinzhou; Wu, Zufang; Li, Chong; Zhang, Xin (Frontiers in Nutrition, 2023)
Aging is a universal and irreversible process, and the skin is an important feature that reflects the aging of the organism. Skin aging has been a focus of attention in recent years because it leads to changes in an individual's external features and the loss of many important biological functions. This experiment investigated the improvement effect of black tea extract (BTE) on the skin of aging mice under D-galactose induction. After six weeks of administration, the changes in skin bio-chemical indices and tissue structure were compared with the blank and positive control groups. It was observed that BTE increased water and hyaluronic acid (HA) content, decreased malondialdehyde (MDA) content, enhanced superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT) activities in the skin of aging mice, and improved the structure of aging damaged skin tissues and increased the content of total collagen. The experimental results showed that BTE can play a significant anti-aging effect on the skin, which can be used as a functional food for aging inhibition.